Recovery of Recurrent Parent Genome in a Marker-Assisted Backcrossing Against Rice Blast and Blight Infections Using Functional Markers and SSRs - Chukwu, Samuel Chibuike (Plants (Basel), 2020)
The most vital aspect of marker-assisted backcross breeding is the recurrent parent genome recovery. This enables the selection of only parents with recovered recipient/recurrent parent genome in addition to the targeted genes. The recurrent parent genome recovery (RPGR) ensures that non-desirable genomic segments are removed while the gene of interest is sustained in the recombined progenies without further segregations. This work was aimed at quantifying the RPGR of backcross populations with introgression of bacterial leaf blight resistance genes. Putra-1, a Malaysian elite variety, high yielding with inherent resistance to blast but susceptible to bacterial leaf blight (BLB), was crossed with IRBB60 which is resistant to BLB disease. The IRBB60 has four Xoo resistance genes—Xa4, xa5, xa13 and Xa21. Tightly linked polymorphic functional and SSR markers were used for foreground selection at every stage of backcrossing to select progenies with introgressed target genes. Background selection was done to quantify the percentage of RPGR in the selected lines using 79 confirmed polymorphic microsatellites. Result obtained showed that the percentage of RPGR was 80.11% at BC(1)F(1), 95.30% at BC(2)F(1) and 95.9% at BC(2)F(2). The introgression of Xa4, xa5, xa13 and Xa21 Xoo resistance genes were faster through the adopted marker-assisted backcross breeding compared to what could be obtained through conventional breeding. All the 16 selected lines displayed resistance to BLB with three lines showing high resistance to the disease. The blast resistance contained in the genetic background of Putra-1 was also sustained in all the selected lines. The newly developed lines were recommended as new rice varieties for commercial cultivation.